Design of Low-Profile Single- and Dual-Band Antennas for IoT Applications - Wazie M. Abdulkawi (MDPI AG, 2021)
This paper presents novel low-cost single- and dual-band microstrip patch antennas. The proposed antennas are realized on a square microstrip patch etched symmetrically with four slots. The antenna is designed to have low cost and reduced size to use in Internet of things (IoT) applications. The antennas provide a reconfigurable architecture that allows operation in different wireless communication bands. The proposed structure can be adjusted to operate either in single band or in dual-band operation. Two prototypes are implemented and evaluated. The first structure works at a single resonance frequency (f1 = 2.4 GHz); however, the second configuration works at two resonance frequencies (f1 = 2.4 GHz and f2 = 2.8 GHz) within the same size. These antennas use a low-cost FR-4 dielectric substrate. The 2.4 GHz is allotted for the industrial, scientific, and medical (ISM) band, and the 2.8 GHz is allocated to verify the concept and can be adjusted to meet the user’s requirements. The measurement of the fabricated antennas closely matches the simulated results.